Égalité, complémentarité, concurrence. La violence entre les “sexes” au Sénégal à l’épreuve du “genre” - Giovanna Cavatorta (Archivio Antropologico Mediterraneo)
This article questions the dynamics of representation and transformation of the power relations between genders in Senegal, by accounting for how they articulate with its political agenda on gender equality. Firstly, it shows the ambivalence and ambiguities of the way in which the experts interpret it. On the one hand, they continue to talk about the female “sex”, thus reinforcing the model of sexual identity and arising in men a problematic feeling of exclusion and victimization. On the other hand, they convey the idea that gender-based violence can be dissociated by the asymmetries of power due to genderization. Thanks to the analysis of a trial for conjugal violence, the essay discusses the stakes of power that are brought to light by its genderization. The article thus shows the importance of considering the anthropo-logical meanings on personhood, gender distinction and injustice, in a broader sense the moral economy of marriage.